Original paper Bronchial reactivity in school children with food allergy in infancy - Krogulska, Aneta; Białek, Jakub; Wąsowska-Królikowska, Krystyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Sensitization to food allergens in early childhood is a risk factor for airborne sensitization and the development of asthma later in life. What underlies this phenomenon is not exactly known so far. It is also not clear what mechanism may predispose children with food allergies to develop asthma later in life. Aim : To assess bronchial hyperreactivity in school-age children with food allergy in infancy. Material and methods: This retrospective study included 158 children aged 7-18 years, who were diagnosed due to the suspicion of allergy in the Department of Allergology, Gastroenterology and Nutrition, Medical University of Lodz. The study was conducted on children suffering from atopic dermatitis, asthma or allergic rhinitis, in which parents reported the presence of food allergy in infancy. The methodology used: a questionnaire survey, medical examination, skin tests (Allergopharma, Reinbek, Germany), spirometry (spirometer Lungtest 1000, MES), and methacholine provocation tests (MP Biomedicals), using inhalant allergy Provocations System MES. Results: A positive result of the methacholine challenge test was obtained in 33, i.e. in 63.5% of children in the study group and in 30 children (50%) in the control group (p > 0.05). Bronchial hyperreactivity occurred significantly more often in children with asthma (20 children, i.e. 95.2%) compared to children with atopic dermatitis (7, i.e. 43.7% of children), as well as compared to children with rhinitis (6 or 40% children) in the study group (p < 0.001, p 0.05). Conclusions : Airway hyperresponsiveness in school children with allergic diseases is not directly dependent on food allergy in infancy.